Goshen Road : a novel - Proudfoot, Bonnie, 1954- (Swallow Press, Ohio University Press, 2020)
"Goshen Road is an elegiac, unvarnished, and empathetic portrait of one working-class family over two decades in rural West Virginia, with sisters Dessie and Billie Price as its urgently beating heart. Bonnie Proudfoot captures them, their husbands, and their children as they balance on the divide between Appalachia old and new, struggling for survival and reconciling themselves with past hurts and future uncertainties as the economy and culture shift around them. The story opens in 1967 with a logging accident and the teenaged Lux Cranfield's headlong plunge into the courtship of Dessie-a leap he takes not only in the wake of his near-death experience but to exchange his bitter home life for a future with the Prices, a family that appears to have the stability and peace that his own lacks. Within the year Lux and Dessie marry. Meanwhile, Dessie's rebellious younger sister, Billie, fights her way through adolescence with an eye toward an escape of her own, only to land with Lux's friend Alan Ray Munn and settle into a life of hardship. Ultimately, the voices and passions of Dessie, Billie, Lux, Alan Ray, and the Cranfield children build on one another to create an unforgettable chorus about the promises and betrayals of love-and what it takes to preserve a family when everything else is uncertain"--